Biometric data of anatomical structure of vegetative organs of rare, narrowly endemic species Oxytropis almaatensis Bajt. in Trans-Ili Alatau mountains (Kazakhstan) (ҚазҰУ Хабаршысы. Биология сериясы, 2016)
The article presents the features of the anatomical structure and biometric indicators of vegetative organs of rare, narrowly endemic species Oxytropis almaatensis Bajt.. The first population of O.almaatensis was discovered in the Big Almaty Gorge, coordinates: N 43004.864', E 076059.604', altitude 2160 m. The second population was located in the Small Almaty Gorge, coordinates: N 43008.490', E 077004.198', altitude 2002 m. The study of anatomical structure of virginal, young and middle-generative O.almaatensis species was comparatively carried out in two populations. In the first and second populations of the virginal age period, it was revealed that the cortex thickness is bigger than in the young and middle-generative periods. The study of the stem internal structure of different age periods in different populations showed that all individuals have the bundle structure of the stem that is characteristic of dicotyledonous plants with varying degrees of development of various tissues. By comparing the anatomical structure of the leaf blades from different populations, it was found that for all individuals of different age periods the dorsoventral, bilateral mesophyll are characteristic.